The Lived Experience of Parents' Receiving the Diagnosis of CDKL5 Deficiency Disorder for Their Child. (May 2022) - Demarest, Scott; Marsh, Rebekah; Treat, Lauren; Fisher, Michael P.; Dempsey, Amanda; Junaid, Mohammed; Downs, Jenny; Leonard, Helen; Benke, Tim; Morris, Megan A.
CDKL5 deficiency disorder (CDD), a severe developmental and epileptic encephalopathy, is being diagnosed earlier with improved access to genetic testing, but this may also have unanticipated impacts on parents' experience receiving the diagnosis. This study explores the lived experience of parents receiving a diagnosis of CDD for their child using mixed methods. Thirty-seven semistructured interviews were conducted with parents of children with a diagnosis of CDD, which were coded and analyzed to identify themes. Grief was a nearly universal theme expressed among participants. Parents of younger children discussed grief in the context of receiving the diagnosis, whereas parents of older children indicated they were at different stages along the grieving journey when they received the diagnosis. Parents with less understanding of their child's prognosis (poorer prognostic awareness) connected their grief to receiving the diagnosis as this brought a clear understanding of the prognosis. Several themes suggested what providers did well to improve the diagnostic experience for parents, much of which aligns with existing literature around how to provide serious news. Additionally, parents identified long-term benefits of having a diagnosis for their child's medical problems. Although interview data were concordant with a survey of parents' diagnostic experience from a large international cohort, most participants in this study were relatively affluent, white mothers and further research is needed to better understand if other groups of parents have a different diagnostic experience. This study gives context of parental experience that providers should be aware of when conveying new genetic diagnoses to families.